The ethical significance of antibiotic resistance towards aquaculture practices - Khan Chowdhury, Ahmed Jalal; John, Akbar; Nasrin, Dilruba; Abdulahi Hashi, Abdurezak; Mohd Omar, Suhaila; Mansor, Nur Nazifah (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
In recent decade, aquaculture species, including fish are under danger from bio-aggressors like viruses, bacteria, parasites and fungi. These organisms harm either spontaneously or through aquatic animal husbandry practices or both. The chemicals employed in aquaculture are drugs like antibiotics used to treat diseases, chemicals introduced through construction materials and hormones used to alter the reproductive viability, sex and growth rates. Drugs used to treat disease are the most dangerous to the fish. These persistent antibiotics tend to increase antibiotic-resistant free-living bacteria, thereby altering the composition of normal marine and freshwater bacterial flora. Evidence suggests that these antibiotic-resistant organisms in the marine environment will, in turn, pass their antibiotic resistance genes to other bacteria including human and animal pathogens. Antibiotic treatment in aquaculture is achieved by medicated baths and medicated food. In both cases, the probability exists for antibiotics to pass into the environment, affecting wildlife, remaining in the environment for extended periods of time and exerting their antibiotic effects to human. In this manner, potential alterations of the diversity of the marine micro-biota produced by antibiotics may alter the homeostasis of the marine environment and affect complex forms of life including fish, shellfish, marine mammals, and human beings. The contamination of surface waters with antimicrobials has become an increasing public health concern because of the emergence of multi-resistant pathogens. Efforts to make progress on these issues require us to raise, confront and enact some difficult ethical decisions that will affect the living standard of human. Nevertheless, excessive antibiotic use in aquaculture should be of high concern to the aquaculture industry and its regulators, to public officials dealing with human and animal health and with the preservation of the environment, and to non-governmental organizations dealing with these issues.